Modelling of Wireless Network Coding - Svobodník, P. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
During data exchange in the Point-to-Point wireless topology, in case where end nodes aren’t accessible directly, a relay is deployed. However, the basic approach to relays – Store-andForward – isn’t the way to reach the maximum throughput. Network Coding operation is performed by combining data words (packets) travelling through the network in opposite directions into one packet. End nodes, with knowledge of the data sent, can decode received packet. Packet exchange is then finished in shorter time which results in an increase of network throughput. There are more methods of Network Coding which differ from each other in the time requirements or the ability to work in a noisy channel. In this paper they will be described and compared.
Keywords: Data Flow; Wireless channel; Wireless Network Coding; Decode-and-Forward; Amplifyand-Forward; Denoise-and-Forward